2011
DOI: 10.1364/oe.19.001749
|View full text |Cite
|
Sign up to set email alerts
|

Efficient near-infrared quantum cutting in NaYF_4: Ho^3+, Yb^3+ for solar photovoltaics

Abstract: Quantum cutting converting a ultraviolet photon into two near-infrared photons has been demonstrated by spectroscopic measurements in NaYF4:Ho3+,Yb3+ synthesized by hydrothermal method. Evidence is provided to confirm the occurrence of quantum cutting. Upon excitation of Ho3+ 5G4 level, near-infrared quantum cutting could occur through a two-step resonance energy transfer from Ho3+ to Yb3+ by cross relaxation, with a maximum quantum efficiency of 155.2%. This result reveals the possibility of violet to near-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
77
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 142 publications
(83 citation statements)
references
References 17 publications
5
77
1
Order By: Relevance
“…1(b)), NIR emission at 850 nm disappears expectedly. 21 18,19 whereas that of 985 nm PL rises before Yb 3+ content reaching the concentration quenching threshold 10 mol.% and that of 1180 nm emission increases monotonically. In comparison, PL spectrum of β-NaYF 4 :Ho 3+ excited at 880 nm ( Fig.…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“…1(b)), NIR emission at 850 nm disappears expectedly. 21 18,19 whereas that of 985 nm PL rises before Yb 3+ content reaching the concentration quenching threshold 10 mol.% and that of 1180 nm emission increases monotonically. In comparison, PL spectrum of β-NaYF 4 :Ho 3+ excited at 880 nm ( Fig.…”
Section: Resultsmentioning
confidence: 94%
“…Noted that, as Yb 3+ content increases, PL intensity of ∼850 nm for Ho 3+ : 3 D 3 → 3 K 8 , 5 F 2 also decreases monotonically but that of 1180 nm for Ho 3+ : 5 I 6 → 5 I 8 enhances gradually. 19 In order to further investigate the NIR emission schemes in β-NaYF 4 :Ho 3+ ,Yb 3+ , NIR PL spectra (Figs. 1(b)-1(c)) were recorded for 535 and 880 nm excitation, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…With 359 nm excitation, nearinfrared QC could occur through cross-relaxation in a twostep resonance energy transfer from Ho to Yb, with a maximum QE of 155.2%. Yu et al 80 observed QC in hexagonal beta-NaYF 4 doped with Ho:Yb by exciting with 300-550 nm, yielding two NIR photons. It was found that NIR-QC can occur via two energy transfer mechanisms: through the simultaneous excitation of two Yb ions via cooperative energy transfer and via resonant energy transfer followed by a sequential 5 84 Detailed information on various upconversion and downconversion materials that can be used for solar cell can be found in Ref.…”
Section: Solar Cellsmentioning
confidence: 99%